Stat1 Expression is an Independent Indicator of Prognosis in Lymph node Positive Breast Carcinomas - Z Madjd; A Al -Atta; NFS Watson; I Spendlove; I Ellis; LG Durrant (Tehran University of Medical Sciences, 2005)
Introduction: STAT-1 is the main signal transducer of γIFN signalling through the IFGNR1. STAT-1 can act as a tumour suppressor by induction of the cycle inhibitors p27 and p21 and proapoptotic signals such as casapse 1. Both γIFN knockout mice and STAT-1 knockout mice show enhanced susceptibility to both carcinogen induced and spontaneous tumour formation implying that immune surveillance by this pathways is an important extrinsic tumour suppressor factor. Tumours that become resistant to this pathway by a process of "immune editing" may have a worse prognosis. Methods: In the present study, we have determined the immunohistochemical expression of IFNGR1, STAT1, p27 and p21 in a 730-specimen breast tissue array. These specimens comprise a well characterized series of patients (70 years of age or less, mean: 54) with primary operable breast cancer, diagnosed between 1987 and 1992. Results: All tumours expressed IFNGR1. Cytoplasmic and nuclear expression of STAT1 was detected in 312/730 (42.7%) and 148/730 (20.3%) of breast tumours respectively. Survival analysis demonstrated that patients with tumours with low STAT1 expression (either nuclear or cytoplasmic) had an improved survival compared with those with higher expression (log rank test, P= 0.03). In accordance, multivariate analysis using Cox regression in lymph node positive patients revealed that low expression of STAT1 was independently associated with a good prognosis (HR 0.425, 95% CI 0.225-0.802, P= 0.008). As STAT-1 has a very short half-life its expression is undetectable in normal tissues. In contrast, hyperactivation or mutation may result in an increased half-life but abnormal signal transduction. To assess if STAT-1 was active co-expression of p21 and p27 were also measured. Tumours expressing STAT-1 but not expressing either p27 or p21 had a significantly worse survival than STAT-1+ p21/p27+ tumours or STAT-1 - p21/p21+ or STAT-1- p21/p27- tumours. Conclusion: This study expression of STAT-1 is an independent prognostic marker predicting poor survival in lymph node positive beast cancer. As STAT-1 cannot be detected by immunohistochemistry in normal tissues due to its short half-life, expression in tumours implies abnormal expression. Perhaps breast tumours respond to immunosurveillance within lymph nodes by selection of variants with abnormal STAT-1 regulation which allows them to escape immune recognition.